Enhancing Financial Literacy Through Audio-Visual Learning: The Impact of Short Films on Students’ Understanding of the Rupiah - Fany Octaviany; Sholeh Hidayat; Lukman Nulhakim (STAI Hubbulwathan Duri, 2025)
In the globalization era, financial literacy education is essential for high school students. However, many still lack understanding of basic economic concepts, particularly the value and role of the rupiah. This study investigates the effectiveness of short films as an audio-visual medium to improve students’ comprehension of Cinta Rupiah. This research employed a mixed-methods approach involving 34 tenth-grade students at SMAN 2 KS Cilegon. Quantitative data were collected using pre-tests and post-tests, while qualitative insights were obtained through classroom observations and semi-structured interviews. A paired t-test was applied to analyze differences in student achievement before and after the intervention. Findings showed a significant improvement in students’ financial understanding. The average pre-test score of 56.7 increased to 82.3 in the post-test, with statistical analysis confirming significance (p = 0.001, p 0.05). Observational data revealed higher classroom engagement, with students participating more actively during discussions when short films were used compared to traditional lectures. Interviews indicated that visual storytelling helped students grasp abstract economic concepts more easily by evoking emotions and connecting with their real-life experiences. The results highlight the pedagogical value of short films in making financial literacy learning more engaging and contextual. Unlike conventional methods, narrative-driven audio-visual content fosters deeper comprehension and student motivation. Short films are a feasible and effective alternative for strengthening financial literacy, particularly in fostering appreciation of the rupiah. Broader implementation and development of context-based audio-visual content are recommended to enrich economic education in Indonesia.